Effects of sowing dates and phosphorus levels on cotton growth and yield: soil analysis and implications - Tlatlaa, Jacob Shauri; Tryphone, George Muhamba; Nassary, Eliakira Kisetu (Frontiers in Sustainable Food Systems, 2023)
This study assessed the effects of sowing dates and phosphorus levels on cotton performance in Chato-Msilale village in Chato District, Tanzania. The soil analysis revealed that field exhibited slightly acidic soil with normal electrical conductivity but suffered from severe deficiencies in total nitrogen and organic carbon. The same field presents common issue of low cation exchange capacity, indicating limited nutrient-holding capacity. Furthermore, both fields displayed very low levels of total nitrogen (< 0.1%), signaling a nitrogen deficiency. Available phosphorus was rated as medium (16.8 mg kg -1 soil). Trace elements fluctuated and could be managed based on specific crop requirements. The factors at different levels were: 1. sowing dates -(i) 25 th November 2022, (ii) 15 th December 2022, and (iii) 4 th January 2023; and 2. Phosphorus levels -(i) control, (ii) 20 kg P ha -1 , (iii) 40 kg P ha -1 , and (iv) 60 kg P ha -1 . Regarding cotton growth and yield, sowing dates significantly (P <0.001) influenced plant height, gin turnout, lint yield, number of bolls per plant, and boll weight while phosphorus levels did not exhibit significant effects. Earlier sowing dates resulted in higher yields, albeit with variations in yield components. Interactions showed that growth and yields were only numerically higher in the middle sowing date at higher levels of phosphorus applied. Overall, these insights offer valuable guidance for optimizing cotton cultivation in Chato District, emphasizing the importance of selecting appropriate sowing dates for improved yields.